Crianças, pesca artesanal, trabalho e escola no contexto da Comunidade da Pontinha do Bacuriteua da Amazônia bragantina - OLIVEIRA, Marcos Vinicius Sousa de (2021)
The research analyzes children's discourses the meanings and meanings about artisanal fishing, work and school in a fishing community of the Bragantina Amazon. The study is a qualitative approach of ethnophotographic type. The research has as research locus the Pontinha do Bacuriteua Traditional Community, located around the mangroves of the Caeté-Taperaçu Marine Extractive Reserve (RESEX-MAR), located in Bragança, Pará. data participant observation, conversation wheel, work panel, reading and writing activity and photographic record. Data analysis is supported by the discourse analysis technique in Bakhtin, using the category polyphony. Eleven children aged from 08 to 12 years old, enrolled in Bragança municipal schools, participated in the research. The research findings point to an intense production of children's cultures. It reveals a broad interaction of children with artisanal fishing, work and school in the community. They articulate traditional knowledge articulated school knowledge, revealing the existence of work as an educational principle. Artisanal fishing expressed in children's discourse is the place of joy, play and formation of human existence through content and form, denying the demeaning condition of child labor. The discursive statements align the social experiences of each child in the interaction with the community and environment in which they live. We conclude that the uniqueness of children concerning artisanal fishing allows us to realize that the formative character of fishing is in the relationship between fishing knowledge and school knowledge, affirming the presence of work as a formator of social life in the context of the Pontinha do Bacuriteua Community.